(NsOWREMENNYJ RUSSKIJ QZYK (B:s (Nu^EBNOE POSOBIE (B/s - (NwALXKOWA(B, (Nd(B.(Np(B.s; (NmALOWICKIJ(B, (Nl(B.(Nq(B.s ((NmOSKWA (B:s (NpROSWE]ENIE (B,s, 1986)
(NbIBLIOGR(B. (NW KONCE RAZDELOWs
Keywords: (NrUSSKIJ QZYKs